Continuity of genetic and environmental influences on clinically assessed major depression from ages 18 to 45. Issue 15 (28th November 2018) - Torvik, Fartein Ask; Gustavson, Kristin; Ystrom, Eivind; Rosenström, Tom H.; Gillespie, Nathan; Reichborn-Kjennerud, Ted; Kendler, Kenneth S.
Abstract: Background: Studies on the stability of genetic risk for depression have relied on self-reported symptoms rather than diagnoses and/or short follow-up time. Our aim is to determine to what degree genetic and environmental influences on clinically assessed major depressive disorder (MDD) are stable between age 18 and 45. Methods: A population-based sample of 11 727 twins (6875 women) born between 1967 and 1991 was followed from 2006 to 2015 in health registry data from primary care that included diagnoses provided by treating physicians. Individuals with schizophrenia or bipolar disorder ( n = 163) were excluded. We modelled genetic and environmental risk factors for MDD in an accelerated longitudinal design. Results: The best-fitting model indicated that genetic influences on MDD were completely stable from ages 18 to 45 and explained 38% of the variance. At each age, the environmental risk of MDD was determined by the risk at the preceding observation, plus new environmental risk, with an environmental correlation of +0.60 over 2 years. The model indicated no effects of shared environment and no environmental effects stable throughout the observational period. All long-term stability was therefore explained by genetic factors. Conclusions: Different processes unfolded in the genetic and environmental risk for MDD. The genetic component is stable from later adolescence to middle adulthood and accounted for nearly all long-term stability. Therefore, molecular genetic studies can use age-heterogenous samples when investigating genetic risk variants of MDD. Environmental risk factors were stable over a short span of years with associations rapidly decreasing and no evidence of permanent environmental scarring.